2018
DOI: 10.1007/s00520-018-4362-3
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of the digestive tract mucositis derived from myeloablative and non-myeloablative/reduced-intensity conditionings with busulfan in hematopoietic cell transplantation patient

Abstract: Busulfan is a major component of chemotherapy conditioning in hematopoietic cell transplantation (HCT). This alkylating agent is highly toxic at myeloablative doses, exposing HCT patients to risks of mortality. Non-myeloablative (NMA) and reduced-intensity conditioning (RIC) using busulfan have shown impaired toxicity. However, the toxicity of NMA/RIC in the digestive tract is poorly described. This study aimed to characterize the mucositis in the oral cavity (OM), oropharynx/esophagus, and gastrointestinal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…A higher incidence of grade 3 to 4 OM has been previously observed with myeloablative conditioning compared to reduced intensity conditioning utilizing busulfan-based regimens [13]. In this study, grade 3 to 4 OM was observed in 45% of patients receiving a myeloablative regimen, which is lower than grade 3 to 4…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…A higher incidence of grade 3 to 4 OM has been previously observed with myeloablative conditioning compared to reduced intensity conditioning utilizing busulfan-based regimens [13]. In this study, grade 3 to 4 OM was observed in 45% of patients receiving a myeloablative regimen, which is lower than grade 3 to 4…”
Section: Discussionsupporting
confidence: 38%
“…In recent years, oral microbiome and genetic factors have been suggested as risk determinants for OM [10,11]. Treatmentrelated risk factors have been more frequently analysed in the literature.. Impact of conditioning chemotherapy intensity has con icting data, and it is not clear whether intensity per se is an independent risk factor [9,[12][13][14][15]. Methotrexate (MTX) as an immunosuppressant, and its dose, are consistently reported as a risk factor for OM [14,16,9].…”
Section: Introductionmentioning
confidence: 99%
“…(2006). Busulfan is an important agent used in conditioning for hematopoietic cell transplantation (HCT) (Eduardo et al., 2019). Although different chemotherapeutic agents were described within the protocols used in the studies, many of these agents were combined with others, a fact that increased their toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The alkylating agent busulfan was a potential risk factor for the increase in OM in the study by Fadda et al (2006). Busulfan is an important agent used in conditioning for hematopoietic cell transplantation (HCT) (Eduardo et al, 2019).…”
Section: Ta B L Ementioning
confidence: 99%
“…Regimens typically include an alkylating agent like busulfan (Bu), melphalan or cyclophosphamide (Cy) and a purine analog such as fludarabine (Flu), with or without low-dose TBI. Clinical GI toxicity of RIC transplants is reported to be moderate 22 , 23 , and the associated intestinal epithelial damage 16 , 17 and mucositis 24 have been found to be less severe. The occurrence of aGVHD after RIC is reduced as well 25 .…”
Section: Introductionmentioning
confidence: 99%